ANALISA BENTUK PERMUKAAN PELAT PENYERAP SPONGE TERHADAP KINERJA SOLAR STILL DOUBLE SLOPE TIPE V - alfin amanda alfin amanda; Nova R. Ismail; M. Agus Sahbana (Jurnal Energi dan Teknologi Manufaktur, 2020)
This study aims to determine the surface shape of the sponge absorbent plate to the performance of the solar still double slope type V. The surface shape of the sponge absorbent plate uses sponge models of triangles, fins, waves and flat with a thickness of 5 cm. experimental Tests methods use direct solar radiation and using sea water is used as raw material. The experiment produced 4,527 liters of condensate water with highest solar still efficiency of 50.14% using a sponge wave absorber plate with an area of 13,940.76 cm2. The Sea water disability to flow capillary to the surface of the absorbent plate affecting the performance of solar still.